Interpreting posts in empathic games: assumptions for a conceptual framework - dos Santos, Danilo Barros; Pinheiro, Tânia Saraiva de Melo; Maciel, Cristiano; Rodrigues, Kamila Rios; Nunes, Eunice Pereira dos Santos (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
Games are part of a profitable market, with constant innovations and new technologies to meet users' needs. The understanding of elements related to games is a challenge, especially empathic games, i.e., those that foster users' empathy. This category of games makes users think over delicate and moving themes. This study aims at human interpretations of different sorts of data from discussion forums on empathic games. To do so, we considered ratings of user comments analyzed in previous research with two games, “That Dragon, Cancer” and “Valiant Heart”, and we used an analysis tool. The data patterns allowed theories to emerge, and also allowed us to analyze users' profiles and comments, by reorganizing the previously proposed categories, but now based on assumptions of Grounded Theory. The methodological path points out ways in which the interpretation of the data proved to be useful for the future development of a conceptual framework for creating and evaluating this kind of game.